2006
DOI: 10.1007/s00213-005-0269-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of creatine supplementation and sleep deprivation, with mild exercise, on cognitive and psychomotor performance, mood state, and plasma concentrations of catecholamines and cortisol

Abstract: Following 24-h sleep deprivation, creatine supplementation had a positive effect on mood state and tasks that place a heavy stress on the prefrontal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(90 citation statements)
references
References 37 publications
0
81
0
3
Order By: Relevance
“…The POMS measures individuals' perception of fatigue, vigour, anger, depression and tension. Research evidence suggests that mood state can influence physiological performance, and thus have an affect on climbing performance (Beedie, Terry, & Lane, 2000;McMorris et al, 2006). The reliability of the POMS has been confirmed by Grove and Prapavessis (1992), through comparing the mood states of winners and losers; it was found that all subscales, except fatigue, produced significant differences between these groups.…”
Section: Measures Of Anxiety In Current Climbing Literaturementioning
confidence: 81%
“…The POMS measures individuals' perception of fatigue, vigour, anger, depression and tension. Research evidence suggests that mood state can influence physiological performance, and thus have an affect on climbing performance (Beedie, Terry, & Lane, 2000;McMorris et al, 2006). The reliability of the POMS has been confirmed by Grove and Prapavessis (1992), through comparing the mood states of winners and losers; it was found that all subscales, except fatigue, produced significant differences between these groups.…”
Section: Measures Of Anxiety In Current Climbing Literaturementioning
confidence: 81%
“…Increases in glucose availability, from the ingestion of sugars or the release of the acute stress hormone norepinephrine, improve memory (Wenk 1989;Foster et al 1998), with the effects being particularly pronounced in demanding tasks (Sunram-Lea et al 2002). Creatine, a nutrient that improves energy availability, also appears to benefit overall cognitive performance (Rae et al 2003) and reduce mental fatigue (Watanabe et al 2002;McMorris et al 2006). Besides being an energy source, food can contribute to cognition by providing amino acids needed in the production of neurotransmitters, which is particularly important during periods of stress or sustained concentration (Banderet and Lieberman 1989;Deijen et al 1999;Lieberman 2003).…”
Section: Drugsmentioning
confidence: 99%
“…The authors speculated that creatine supplementation may be beneficial in those with the apoE 14 gene. Earlier McMorris et al (7) had reported in those who were sleep-deprived for 24 h that creatine supplementation had a positive effect on mood and cognition. A review (1) concluded that in experimental paradigms of neurological diseases, supplementation with creatine can reduce neuronal loss.…”
mentioning
confidence: 92%